OBSERVATIONS ON THE BIOLOGY AND FISHERY OF THE INDIAN MACKEREL RASTRELUGER KANAGURTA (CUVIER) FROM ANDAMAN ISLANDS - Luther, G (Indian Journal of Fisheries, 2011)
Rastrelliger kanagurta (Cuvler) seems to spawn in the sea around the Andaman Islands from October to April, an individual fish releasing about three batches of eggs in a season, the time interval between successive spawnings being about one mouth. More ttam 50 % of the fish are raatute at the total length range of 250-259mm. the size of fish at completion of one to five years of life provisionally is estimated as 148mm, 218mm, 265mm, 302 mm and 330mm respectively; A higher average growth rate of 22 mm per month was obtained for juveniles up to 110 mm total length. The growth checks found in scales have been considered to be the spawning marks. The length-weight relationship of the species has beeii estimated. The fish feed mainly on planktonic copepods and other crustaceans. The main mackerel fishery season around the Andaman Islands lasts for four months from May to August, when about 60% of the annual mackerel catch is landed. About 90% of the mackerel in the commercial catches ranged in size between 21 cm and 29 cm of which fish in the 21-24 cm total length range constituted about 60%. Whereas the mackerel fishery season along the west coast of India coincides with the post SouthWest Monsoon period, in the Andamans it coincides with the mid South-West Monsoon Season